PENGARUH METODE DRILL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 1 MONTONG TANGI TAHUN AJARAN 2025/2026 - Safitri, Arini; Atiaturrahmaniah, Atiaturrahmaniah; Ibrahim, Doni Septu Marsa; Kudsiah, Musabihatul (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to examine the effect of the drill method on third-grade students’ mathematics learning outcomes on the topic of length measurement at SD Negeri 1 Montong Tangi in the 2025/2026 academic year. The research employed a quantitative approach using an experimental method with a one-group pretest–posttest design. The instrument consisted of 10 multiple-choice items that had been tested for validity, reliability, discrimination index, and difficulty level. The subjects were one class that received instruction using the drill method. The results showed that the mean score increased from 37.62 in the pretest to 72.38 in the posttest. Tests of normality and linearity indicated that the data were normally distributed and had a linear relationship. Hypothesis testing using the paired samples t-test yielded a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest results. In conclusion, the drill method has a positive and significant effect on improving students’ mathematics learning outcomes.